The effect of the students loan scheme on access to higher education in Ghana: a case of Kwame Nkrumah University of Science and Technology, Kumasi - Alhassan, Sadiq (2016)
A thesis submitted to the Department of Marketing and Corporate Strategy, Kwame Nkrumah University of Science and Technology (KNUST) in partial fulfillment for the award of the degree of Master of Business Administration (Strategic Management and Management Consulting Option),